Learners in transition: a longitudinal study of seven People's Republic of China students at the National University of Singapore - Fong, Yoke Sim (2014)
This doctorate thesis reports on a qualitative research project to investigate the English learning experiences of seven People’s Republic of China (PRC) students during nearly five years of studies at the National University of Singapore (NUS). The research questions for this longitudinal, multiple-case study are: